Antimony resistance mechanism in genetically different clinical isolates of Indian Kala-azar patients - Khanra, Supriya; Das, Shantanabha; Sarraf, Nibedeeta Rani; Datta, Sanchita; Das, Anjan Kumar; Manna, Madhumita; Roy, Syamal (Frontiers in Cellular and Infection Microbiology, 2022)
The central theme of this enterprise is to find common features, if any, displayed by genetically different antimony (Sb) resistant viscerotropic Leishmania parasites to impart Sb resistance. In a limited number of clinical isolates (n=3) we studied the breadth of variation in the following dimensions: (a) intracellular thiol content, (b) cell surface expression of glycan having N-acetyl-D-galactosaminyl residue as the terminal sugar, and (c) gene expression of thiol synthesizing enzymes (CBS, MST, gamma-GCS, ODC and TR), antimony reducing enzymes (TDR and ACR2) and antimonial transporter genes (AQP1, MRPA, PRP1). One of the isolates, T5 that was genotypically characterized as L. tropica caused Indian Kala-azar and was phenotypically Sb resistant (T5-LT-SSG-R) while the other two were L. donovani out of which one isolate, AG83 is antimony sensitive (AG83-LD-SSG-S) and the other isolate T8 is Sb resistant (T8-LD-SSG-R). Our study showed that the Sb resistant parasites regardless of their genotype, showed significantly higher intracellular thiol as compared to Sb sensitive AG83-LD-SSG-S. Seemingly, T5-LT-SSG-R showed about 1.9-fold higher thiol content as compared to T8-LD-SSG-R which essentially mirrored cell surface N-acetyl-D-galactosaminyl expression. Except TR, expression of remaining thiol synthesizing genes were significantly higher in T8-LD-SSG-R and T5-LT-SSG-R than the sensitive one and between the Sb-resistant parasites, the later showed significantly higher expression. Furthermore, genes for Sb reducing enzymes increased significantly in resistant parasites regardless of genotype as compared to the sensitive one and between two resistant parasites there was hardly any difference in expression. Out of three antimony transporters, AQP1 was decreased with the concurrent increase in MRPA and PRP1 in resistant isolates when compared to the sensitive counterpart. Interestingly no difference in expression of the above transporters was noted between two Sb resistant isolates. The enduring image that resonated from our study is that the genetically diverse Sb-resistant parasites showed enhanced thiol synthesizing and antimony transporters gene expression than the sensitive counterpart to confer resistance phenotype.